Порівняння вітчизняних і закордонних методів обліку надходження й вибуття запасів та можливість їх використання в Україні - Shmatkovska, Tetiana О.; Шматковська, Тетяна Олександрівна; Коваль, Н. І.; Koval, N. I. (Придніпровська державна академія будівництва та архітектури, 2016)
In article there are comparison of foreign and domestic experience of stock accounting. Advantages and disadvantages of permanent and periodic system of their accounting are determined. The main accounting methods of disposal of stocks in Ukraine and abroad are considered. Benefits and shortcomings of their use at the entities of various type are determined. The possibility of use of foreign experience of stock accounting in Ukraine is researched.У статті здійснено порівняння закордонного та вітчизняного досвіду обліку запасів. Визначено переваги й недоліки постійної та періодичної системи їх обліку. Розглянуто основні методи обліку вибуття запасів в Україні та за кордоном. Визначено переваги та недоліки їх використання на підприємствах різного типу. Досліджено можливість використання закордонного досвіду обліку запасів в Україні.
Comparison of domestic and foreign accounting methods of inflows and outflows of stocks and possibility of their use in Ukraine
Keywords: stocks; запаси; stock accounting; облік запасів; outflows of stocks; вибуття запасів; methods of depreciation reserves; методи списання вартості запасів; periodic system; періодична система